Gastroenteropancreatic neuroendocrine tumor of the accessory papilla of the duodenum: a case report - Kosei Takagi; Yuzo Umeda; Ryuichi Yoshida; Kazuhiro Yoshida; Kazuya Yasui; Hiroki Sato; Takahito Yagi; Toshiyoshi Fujiwara (Surgical Case Reports, 2021)
Abstract Background Contrary to the increasing incidence of gastroenteropancreatic neuroendocrine tumors (GEP-NETs), GEP-NETs of the accessory papilla of the duodenum are extremely rare. Furthermore, there have been no recommendations regarding the treatment strategy for GEP-NETs of the accessory papilla of the duodenum. We present a case of GEP-NET of the accessory papilla of the duodenum successfully treated with robotic pancreatoduodenectomy. Case presentation A case of a 70-year-old complaining of no symptoms was diagnosed with GEP-NET of the accessory papilla of the duodenum. A 8-mm tumor was located at the submucosal layer with a biopsy demonstrating a neuroendocrine tumor grade 1. The patient underwent robotic pancreatoduodenectomy as curative resection for the tumor. The total operative time was 406 min with an estimated blood loss of 150 mL. The histological examination revealed a well-differentiated neuroendocrine tumor with low Ki-67 index (< 1%). In the posterior areas of the pancreas, the lymph node metastases were detected. The patient was followed up for 6 months with no recurrence postoperatively. Conclusions Considering the potential risks of the lymph node metastases, the standard treatment strategy for GEP-NETs of the accessory papilla of the duodenum should be radical resection with pancreatoduodenectomy. Minimally invasive approach can be the alternative to the conventional open surgery.